Adherence in dermatology - Davis, Scott A. (Adis, Springer, 2016)
An essential, comprehensive, and practical guide to understanding, measuring, and modifying patients' adherence behavior to optimize treatment outcomes, this book covers all major aspects of adherence in dermatology.